Discouraged and hedged – why students enter VET after obtaining university eligibility - Hartung, Andreas [Verfasser]; Weßling, Katarina [Verfasser] (My University, 2024)
„Approximately 25% of vocational education and training (VET) applicants in Germany hold a university entrance diploma (Abitur). These students enter VET even though they could enter higher education (HE); the latter typically yields higher incomes and better career prospects. We extend research on the question of why students choose this seemingly less optimal career path by exploring the interplay between local labour-market conditions and social background. We focus on students’ path through (post-)secondary school and combine data from the German National Educational Panel Study (NEPS) with regionalised data to analyse students’ (1) aspirations for an Abitur in 9th grade, (2) chances of obtaining an Abitur (3), aspirations for HE over VET in 12th grade and (4) the transition to HE versus VET after obtaining an Abitur. Our results speak to the presence of two theoretical concepts: the ‘discouraged worker effect’ and ‘hedging’. In tight local labour markets, students from lower-status families are discouraged from entering VET and continue in general school. Hence, they aspire an Abitur and obtain an Abitur to avoid the VET market at first. Later, they use their Abitur as a hedge to take advantage of this higher educational credential in contested VET markets.“ (authors‘ abstract.; BIBB-Doku)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; G 1.3.2 Bildungsverhalten und -verläufe; 370; 300; Abiturient; Studienberechtigter; Bildungsentscheidung; Berufsausbildung; Bildungsaspirationen; Einflussfaktor; Regionaler Arbeitsmarkt; Sozialer Status; Nationales Bildungspanel